Experimental investigation of vegetal and synthetic fabrics cohesion in order to prevent the tow sliding defect via frictional and pull-out test. (December 2020) - Salem, M.M.; De Luycker, E.; Delbe, K.; Fazzini, M.; Ouagne, P.
Abstract: The tow-sliding defect also referred to as gapping that appears during complex shaping of woven reinforcements is due to a loss of cohesion in the fabric. The cohesion of the fabric tends to keep the tows from sliding under tension. This cohesion depends on the frictional behavior of the tows mainly. Other factors such as the weave of the fabric, the tensions and shear state of the fabric during forming play an important role as well. An analysis of the frictional behaviors of the tows coupled to out of plane pull-out tests to determine the influence the aforementioned parameters on the cohesion of the reinforcements was then carried out. It was showed that the cohesion of the fabric, limiting the risk of appearance of tow sliding defect, can be improved by increasing the transverse tow tension in low shear region, and by the in-plane shear itself in highly sheared zones.